A study on Filipino men's sizes on trousers - Vergara, Shiella R.; Florendo, Raquel Baltazar (1998.)
The growth and development of the garment industry in the Philippines is not only reflected in the new manufacturing methods, the change in clothing production and the advances in machinery, but also in the type, size and fit of clothing. These advances and changes produced an awareness of the changing figure which necessitated new definitions and revisions and expansion of the classification of figure types and size ranges within the classifications. This study purports firstly, to determine the standard body measurement of Filipino men with regards to sizing on ready-to-wear clothing, specifically on trousers. The study also gives an overview of the different sizing system of local government manufacturers. The objectives of the study are to provide a standard classification of body measurements and sizing on trousers and to resolve the inconsistensies and discrepancies of measurements for sizing on trousers The subjects for the study were Filipino men on average build, 5 feet - 3" feet - 7" in height and between the range of 21 to 30 years old. The method was to measure all male subjects using ISO's standard procedure for measuring the body. Body measurements that were considered were the waist, hip and inside leg length. The statistical method that was used after obtaining the necessary data was cluster analysis. In this, the gathered data were grouped into clusters according to the similarities of body measurements. The result yielded 21 clusters and shows that age and height were not a factor in determining body measurements or a tall person can have smaller body measurements that a short person. This result repeals the notion that a person whose short in height belongs to a small size and taller persons belong to a medium or large size. The result was able to answer the main objective of this study, that is to provide a classification of body measurements on trousers.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Trousers